1978
DOI: 10.1093/jn/108.6.936
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Excess Dietary L-Histidine on Plasma Cholesterol Levels in Weanling Rats

Abstract: Supplementation of a closed formula, cereal based stock diet with excess L-histidine at a 5% or 8% level for 4 days reduced growth and induced hepatomegaly and an increase in plasma cholesterole levels in weanling rats. The enlargement of the liver was in part due to glycogen accumulation; plasma glucose concentration was unchanged. Feeding four different amino acids (L-phenylalanine, L-glutamic acid, glycine and L-tryptophan), at levels which caused reduction of growth comparable to the 5% and 8% L-histidine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 9 publications
1
20
0
1
Order By: Relevance
“…It follows from these observations that the decrease in serum glucose might have been due to the accumulation of glycogen in the liver. 3 ) Thus, the response of serum glucose in young rats to excess histidine under the non-starved state was different from that in adult rats. We have no adequate explanation for the reason why liver glycogen accumulates in rats fed with a histidine-exce~s diet.…”
Section: Serum Glucosementioning
confidence: 95%
“…It follows from these observations that the decrease in serum glucose might have been due to the accumulation of glycogen in the liver. 3 ) Thus, the response of serum glucose in young rats to excess histidine under the non-starved state was different from that in adult rats. We have no adequate explanation for the reason why liver glycogen accumulates in rats fed with a histidine-exce~s diet.…”
Section: Serum Glucosementioning
confidence: 95%
“…It seems likely that cholesterol metabolism is quite different in rats fed higher doses of tyrosine from those of rats fed cholesterol-containing diet. Many investigators have already suggested that the hypercholesterolemia seen in feeding dietary tyrosine (Qureshi et al, 1978;Solomon and Geison, 1978) was mediated by enhancement of of cholesterol synthesis in the liver.…”
Section: The Effects Of Tyrosine Supplemented Diet On the Hdl Levels mentioning
confidence: 99%
“…2 Katayama Chemical Industries Co., Ltd., Osaka, Japan. 3 Tokyo Chemical Industry Co., Ltd., Tokyo, Japan. 4 Avicel, Funakoshi Pharmaceutical Co., Ltd., Tokyo, Japan.…”
Section: 68±0wmentioning
confidence: 99%
“…Geison and Waisman 2 ) showed the increase in plasma cholesterol of rabbits fed a histidine-excess diet. Furthermore, Solomon and Geison 3 ) and Harvey et al 4 ) reported that feeding a diet supplemented with excess histidine, but not with other excess amino acids tested, resulted in hypercholesterolemia and hepatomegaly in rats.…”
mentioning
confidence: 99%